Nursing Problems of a Patient with ALS Syndrome — A Case Report - Anna Karłowicz; Katarzyna Ziejka (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The motor-neurone disease Amyotrophic Lateral Sclerosis (ALS) includes slowly progressive disorders with a waveform which is the result of pathologies involving neurones in the cerebral cortex, brain stem and spinal cord. Its severe course is associated with damage to certain brain functions responsible for controlling important vital signs. ALS is an incurable disease that belongs to the neurodegenerative disorders. Due to the progressive nature of the disease, the nurse plays an important role in patient care — from the stage of diagnosis to palliative care. The main objective of the study is to present nursing problems and tasks undertaken by a nurse in the process of nurturing a patient with ALS. Case Report. A man, 42, admitted to the Rehabilitation Clinic of the University Clinic Centre in Gdansk, due to the massive para paresis, upper extremity paralysis more pronounced on the left side. On the basis of clinical picture, there was a suspicion of ALS. Discussion. The presented ALS case with laboratory abnormalities having uncertain meaning (ALS-LAUS syndrome) was characterised by an unusually fast progressing course. Conclusions. The importance of the role of a nurse in the care of the patient with ALS is confirmed by the conclusions reached in the presented case description: 1) The patient was found to have limited physical fitness, communication problems, high risk of developing pressure ulcers and complications associated with immobility. 2) Due to the significantly reduced efficiency of self-service, the patient required a holistic nursing care with regard to activities of daily living. 3) After the hospitalisation the patient required continuity of comprehensive care ensured by the family and support institutions related to home respiratory care. (JNNN 2015;4(4):170–177)